The Effect of Compensation, Career Development, and Work-Life Balance on Employee Loyalty With Job Satisfaction As An Intervening Variable - Reners Reners; Pahlawansjah Harahap; Rini Sugiarti (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to examine and analyze whether compensation, career development, and work-life balance variables influence employee loyalty at Intan Husada Hospital in Garut through the variable of job satisfaction. Data collection in this research used a questionnaire with a total sample of 118 healthcare professionals at Intan Husada Hospital in Garut. This research employs a quantitative approach with the Partial Least Squares Structural Equation Modeling (SEM) analysis method. Exogenous variables in this study are compensation, career development, and work-life balance, the mediating variable used is job satisfaction, while the endogenous variable used is employee loyalty. The direct effect testing results of this study indicate that the compensation and career development variables have a positive but not significant impact on the job satisfaction variable, while the work-life balance variable has a significant positive impact on the job satisfaction variable. Furthermore, the compensation, career development, and work-life balance variables have a positive but not significant impact on the employee loyalty variable, while the job satisfaction variable has a significant positive impact on the employee loyalty variable. The testing of the indirect effect in this study shows that job satisfaction does not play a mediating role in influencing compensation, career development, and work-life balance on employee loyalty